Proses Pembentukan Kompositum pada Nama Objek Wisata Cianjur sebagai Materi Ajar Tata Bahasa BIPA Dasar - Afina Naufalia; Wagiati Wagiati; Ypsi Soeria Soemantri; Puspa Mirani Kadir (Lembaga Sosial Rumah Indonesia, 2022)
This research is motivated by the uniqueness of naming tourist objects in Cianjur Regency which uses a lot of composites. The results of this study can be used as learning materials in BIPA learning. In BIPA learning, according to Permendikbud no. 27 of 2017, there is compound word material and tourism object material in competency element 6.5, so that the design of this grammatical material is sustainable. The method used in this research is descriptive qualitative. The result is that the names of tourist objects in Cianjur are mostly endocentric noun composites which are composed of noun+noun categories and are unequal composites. This data is classified into 8 parts, namely there are 26 composites which are composed of noun+noun categories and are unequal composites, namely compound words whose elements are not equal. This collection of tourist-themed composites can be used as teaching materials for BIPA 3.